Provision of healthy school meals does not affect the metabolic syndrome score in 8–11-year-old children, but reduces cardiometabolic risk markers despite increasing waist circumference. Issue 11 (17th October 2014) - Damsgaard, Camilla T.; Dalskov, Stine-Mathilde; Laursen, Rikke P.; Ritz, Christian; Hjorth, Mads F.; Lauritzen, Lotte; Sørensen, Louise B.; Petersen, Rikke A.; Andersen, Malene R.; Stender, Steen; Andersen, Rikke; Tetens, Inge; et al.
Abstract : An increasing number of children are exhibiting features of the metabolic syndrome (MetS) including abdominal fatness, hypertension, adverse lipid profile and insulin resistance. Healthy eating practices during school hours may improve the cardiometabolic profile, but there is a lack of evidence. In the present study, the effect of provision of school meals rich in fish, vegetables and fibre on a MetS score (primary outcome) and on individual cardiometabolic markers and body composition (secondary outcomes) was investigated in 834 Danish school children. The study was carried out as a cluster-randomised, controlled, non-blinded, cross-over trial at nine schools. Children aged 8–11 years received freshly prepared school lunch and snacks or usual packed lunch from home (control) each for 3 months. Dietary intake, physical activity, cardiometabolic markers and body composition were measured at baseline and after each dietary period. The school meals did not affect the MetS score ( P = 1·00). However, it was found that mean arterial pressure was reduced by 0·4 (95 % CI 0·0, 0·8) mmHg ( P = 0·04), fasting total cholesterol concentrations by 0·05 (95 % CI 0·02, 0·08) mmol/l ( P = 0·001), HDL-cholesterol concentrations by 0·02 (95 % CI 0·00, 0·03) mmol/l, TAG concentrations by 0·02 (95 % CI 0·00, 0·04) mmol/l (both P < 0·05), and homeostasis model of assessment-insulin resistance by 0·10 (95 % CI 0·04, 0·16) points ( P = 0·001) compared with the control diet in the intention-to-treat analyses. Waist circumference increased 0·5 (95 % CI 0·3, 0·7) cm ( P < 0·001), but BMI z -score remained unaffected. Complete-case analyses and analyses adjusted for household educational level, pubertal status and physical activity confirmed the results. In conclusion, the school meals did not affect the MetS score in 8–11-year-olds, as small improvements in blood pressure, TAG concentrations and insulin resistance were counterbalanced by slight undesired effects on waist circumference and HDL-cholesterol concentrations.